Failure of Mediation Implementation In District Court - Primasari, Imas Khaeriyah (Gema Wiralodra, 2025)
This study discusses the failure of mediation implementation in district courts, aiming to identify the factors behind these failures. The research was motivated by the frequent unsuccessful mediation processes in district courts. Using a qualitative approach with descriptive analysis, the study found that the main cause of mediation failure in district courts is legal culture, which can be divided into external and internal factors. Internally, many mediator judges are indifferent, lack seriousness, and treat mediation merely as a formality in fulfilling their duties. Externally, parties involved often prioritize prestige, ego, and self-esteem, believing it is more honorable to proceed to trial rather than settle through mediation.